Nitrogen and phosphorus effects on the growth, phenology, heat and nutrients accumulation and yield of winter maize (Zea mays) in western Indo-Gangetic Plains - NSANZABAGANWA, EPIMAQUE; DAS, T K; RANA, D S (The Indian Journal of Agricultural Sciences, 2014)
The results show that plant height, dry weight, crop growth rate (CGR) and leaf area index (LAI) of winter maize were increased with the increase in N levels, the highest values observed at the highest dose of 240 kg/ha. Nitrogen stress delayed tasseling and silking, but hastened maturity of maize. Nitrogen application at each dose tested caused a significant increase in grain yield over control, the highest increase was at 240 kg/ha. The effect of P on grain yield was also significant, and the highest yield was obtained at 26.4 kg/ha after which further increase in P level declined the yield. Thus, N and P individually and interactively influenced growth variables, appearance of phenological stages, heat and nutrient accumulation and yield in winter maize. The interaction between N and P for LAI, nutrient content and dry matter and heat accumulation was observed across physiological stages with higher values of most of these parameters observed at N 240 kg/ha and P 26.4 kg/ha. It is, therefore, concluded that, a combination of N 240 or 160 (being comparable with 240 kg/ha) kg/ha and P 26.4 kg/ha may be recommended for a significant improvement in winter maize growth, yield and nutrient and heat accumulation over a longer growing period under the western IGP conditions.